Batch and Continuous Adsorption of Chromium (VI) from Aqueous Solution Using Alhagi Forks and Tea Husk - Saed, Usama Akram (Nahrain University College of Engineering Journal, 2017)
The removal of Cr(VI) ions from aqueous solution by natural media was directed in a batch adsorption then in continuous operation. Alhagi forks were collected from road side and tea husk was get it from kitchen, these were need times to cleaning from contaminated waste and colors. In batch mode the pH, time of contacting, adsorbent dose and initial metal ion concentration were determined for the influence of Cr (VI) on the two media. pH=2 was the best acidity of solution and get 99.5% removal for alhagi forks and 98.5% for tea husk. The equilibrium time also indicated at 30min for alhagi forks and 50min for tea husk and the optimum weight of media were used are 0.5g/50ml from alhagi forks and 0.6g/50ml from tea husk. The breakthrough for alhagi forks is better from tea husk for the same conditions. The Langmuir and Freundlich isotherm models were conducted to describe the isotherm and isotherm constants for the two media. Consequences indicated that adsorption of Cr(VI) consumption could be described by Langmuir and Freundlich equations.